Casa de Lava - Costa, Pedro; Machuel, Emmanuel; DeMedeiros, Inês; DeBankolé, Isaach; Scob, Edith (Second Run, 2012)
Leao, a Cape Verdian man working on a construction site in Portugal has a fall and ends up in a coma. While still comatose, arrangements are made from his hometown to have him sent back. A nurse, Mariana, ready for a change of scene, volunteers to accompany him. Upon her arrival, nothing is as she expects. No one seems to be waiting for Leao. As Mariana waits for someone to turn up, even Leao from out of his coma, she gets increasingly involved with the mysterious community and the intrigue mounts. In fact, "Casa de Lava" recalls "Chinatown", where the nosy outsider steps into a situation that turns out to be much more than was bargained for. [www.dvdbeaver.com]